Critical Thinking Ability of Students of SMAN 2 Padang - Tri Lestari Agus Murianti; Heffi Alberida (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2022)
Education has now entered the 21st Century education. In order to survive in the 21st century, various skills are needed, including the 4C skills which consist of critical thinking and problem-solving skills, creativity and innovation, collaboration, and communication. Critical thinking ability is one of the 21st Century Skills that must be possessed by students. The purpose of this study was to determine the critical thinking skills of students at SMAN 2 Padang. The type of research used is descriptive. The population in this study consisted of all class X students of SMAN 2 Padang for the 2021/2022 academic year. The sample in this study was 50 students of class X at SMAN 2 Padang. The technique of determining this sample is done by simple random sampling technique. The instrument used is a validated critical thinking skills questionnaire. Data analysis used descriptive analysis. From the research results obtained in this study, it shows that the critical thinking skills of class X students of SMAN 2 Padang are classified as very low. This is shown from the acquisition of the percentage of critical thinking skills score 5 (very high) which is 9.77%, score 4 (high) is 6.44%, score 3 (enough) is 16.44%, score 2 (low) is 32, 22%, and a score of 1 (very low) which is 35.11%.